Arc-driven mGRASP highlights CA1 to CA3 synaptic engrams - Murthy, B. K. B.; Somatakis, S.; Ulivi, A. F.; Klimmt, H.; Castello-Waldow, T. P.; Haynes, N.; Huettl, R. E.; Chen, A.; Attardo, Alessio (Frontiers in Behavioral Neuroscience, 2023)
Subpopulations of neurons display increased activity during memory encoding and manipulating the activity of these neurons can induce artificial formation or erasure of memories. Thus, these neurons are thought to be cellular engrams. Moreover, correlated activity between pre- and postsynaptic engram neurons is thought to lead to strengthening of their synaptic connections, thus increasing the probability of neural activity patterns occurring dur¬ing encoding to reoccur at recall. Therefore, synapses between engram neurons can also be considered as a substrate of memory, or a synaptic engram. One can label synaptic engrams by targeting two complementary, non-fluorescent, synapse-targeted GFP fragments separately to the pre- and postsynaptic compartment of engram neurons; the two GFP fragments reconstitute a fluorescent GFP at the synaptic cleft between the engram neurons, thereby highlighting synaptic engrams. In this work we explored a transsynaptic GFP reconstitution system (mGRASP) to label synaptic engrams between hippocampal CA1 and CA3 engram neurons identified by different Immediate-Early Genes: cFos and Arc. We characterized the expression of the cellular and synaptic labels of the mGRASP system upon exposure to a novel environment or learning of a hippocampal-dependent memory task. We found that mGRASP under the control of transgenic ArcCreERT2 labelled synaptic engrams more efficiently than when controlled by viral cFostTA, possibly due to differences in the genetic systems rather than the specific IEG promoters.